Children's Pantun from the Perspective Riffaterre's Semiotics: (Pantun Kanak-kanak dari Perspektif Semiotik Riffaterre) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2018)
This article analyzes 20 vocabulary items from classical and contemporary Malay using concept analysis and an analysis method based on 15 children's pantun from a collection of such poems by Mohamad Nazel Hisham. The Semiotics Theory of Riffaterre is seen as appropriate for analyzing children's pantun based on four aspects of meaning, namely viewing pantun as indirect expressions; applying heuristic and hermeneutic reading concepts, as well as hypograms. The findings reveal that children's pantun contain indirect expressions of poetry, the actual structure and the lexical form and paragraphs can be seen based on heuristic readings, while the actual message and meaning can be traced through heuristic and hermeneutic readings. The application of matrix aspect (MAT), model (MOD) and variant (VAR), and the application of hypogram elements also completes the process of meaning creation. The application of these four aspects of meaning proved successful in helping children to interpret the literal meanings, and reducing difficulties in understanding the intended message, thereby improving their ability to understand the Malay language.Keywords: Children's pantun, Riffaterre's Semiotics, hypograms, heuristic and hermeneutic.